Upaya Peningkatan Hasil Belajar Pendidikan Agama Islam melalui Strategi Pembelajaran Poster Session dan Audio Visual pada Materi Tajhīz Jenazah - Rahmah, Syarifah (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2022)
This Classroom Action Research is motivated by the low value of Islamic Religious Education subjects on the material "Tajhīz Jenazah". This is because students do not understand the material presented by the teacher. Students also have a slow response when learning takes place, so learning outcomes are not optimal. The purpose of this study was to determine whether the Poster and Audio-Visual session learning strategies could improve students' ability to understand the material on Tajhīz Jenazah”, to determine student responses, and to determine learning outcomes. To overcome this situation, the researcher tried to change the Poster Session and Audio-Visual learning strategies which were considered suitable for the learning process so that they could improve students' understanding and response. This type of research is Classroom Action Research using a qualitative descriptive approach. This Classroom Action Research was carried out in two cycles. Each cycle consists of planning, implementation, observation, and reflection. Data collection techniques are tests, observations, and document studies. The research instruments were test sheets, observation checklists, and documentation sheets. The results showed that by using the Poster Session and Audio-Visual learning strategies, student learning outcomes increased. In the first cycle, the number of students who got a complete score was 14 students (46.66%), while 16 students (53.33%) got an incomplete score. The second cycle showed a better increase, that the completeness score to 27 students (90%), there an increase of 36.67%. The implication of this research is that by using Poster Sessions and Audio-Visual learning strategies, the learning outcomes of Islamic Religious Education Subjects on the material "Tajhīz Jenazah" can be increased.